Study on Sharia Compliance Principles in Halal Tourism Business in Bandung Regency: An Implementation of Islamic Business Ethics Principles (Professional Ethics) - Solehudin, Ending; Ahyani, Hisam; Putra, Haris Maiza (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
The purpose of this study is to reveal the sharia compliance of the halal tourism business in Bandung Regency, where halal tourism in its implementation must be carried out by prioritizing the principles of Islamic business ethics (Professional Ethics), meaning that the principles of Islamic business ethics in the context of halal tourism in Bandung Regency must submissive (obedient) in a syar'i, especially in promoting the principles of Islamic business ethics, namely by prioritizing Islamic services with the aim of providing comfort for Muslim tourists in particular. In addition, the principles of Islamic service are expected to be able to realize professional ethics in doing business in an Islamic way, especially in carrying out halal tourism activities, especially for tourism industry players in Bandung Regency. This literature review uses the theory of Islamic business ethics as coined by Hamid Salam and Abdalla Hanafi including: a) Ethics to always convey the truth; b) Ethics to be trusted; c) Ethics to do something sincerely; d) Brotherhood ethics; e) Mastery of science; f) Ethics of Justice. The findings of this study are the principles of Islamic business ethics (professional ethics) in the implementation of the halal tourism business in Bandung Regency referring to the Bandung Regency Regional Regulation (Perda) Number 6 of 2020 concerning Halal Tourism, where there are several principles that must be met in running tourism. Halal in Bandung district which includes: a). set as needed; b). facilitate; c). according to ability; d). gradually; e). priority scale; and f). Inclusive. In addition, there is the concept of the Code of Ethics for Tourism (GCET) or the Global Tourism Code of Ethics as a reference for sustainable tourism development in Bandung Regency which includes economic, social, cultural, and environmental components. This is because Indonesia is not an Islamic country but a country where the majority of the population is Muslim, so it is necessary to prioritize the values of Rahmatan lil 'Alamin in business (muamalah), especially in terms of additional service activities in halal tourism in Bandung Regency. In addition, indicators of sharia compliance in halal tourism in Bandung district are referring to 2 regulations, namely local regulations (perda) Bandung district number 6 of 2020 concerning halal tourism, and DSN-MUI fatwa No: 108/DSN-MUI/2016 concerning guidelines for tourism implementation. based on sharia principles.